2020
DOI: 10.1021/acsami.9b20489
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Ratiometric Fluorescent Metal-Organic Framework Sensor for Calcium Signaling in Human Blood Ionic Concentration Media

Abstract: A two-dimensional fluorescent metal-organic framework (MOF) sensor, TMU-5S, was synthesized by introducing rhodamine B into the framework of TMU-5. This dye-sensitized MOF was explored as a ratiometric fluorescent sensor for Ca2+ signaling in the presence of interfering cations in ionic concentrations similar to that of blood plasma that exhibits exceptional sensitivity and selectivity to Ca2+ and faster response and recovery times than any other reported fluorescent sensor. This can be attributed to strong el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 56 publications
0
18
0
1
Order By: Relevance
“…MOFs are a new class of functional porous materials with inorganic and organic species arranged in a regular pattern. The inorganic component in MOFs is usually a metal or metal oxide node, and the organic part is a multidentate ligand such as a benzene carboxylic acid. The metal and ligand can be arranged in specific patterns to form one-dimensional (1D), two-dimensional (2D), and three-dimensional (3D) nanoporous materials.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs are a new class of functional porous materials with inorganic and organic species arranged in a regular pattern. The inorganic component in MOFs is usually a metal or metal oxide node, and the organic part is a multidentate ligand such as a benzene carboxylic acid. The metal and ligand can be arranged in specific patterns to form one-dimensional (1D), two-dimensional (2D), and three-dimensional (3D) nanoporous materials.…”
Section: Introductionmentioning
confidence: 99%
“…A metal–organic framework (MOF) is a three-dimensional porous nanomaterial. , The high surface area, abundant metal active sites, and convenient modification enable the MOF to be used as an outstanding sensing material candidate in the development of high-performance biosensors. , A typical example is the Zr-based MOF that shows a high affinity toward phosphate groups (−PO 4 3– ) by forming a strong Zr–O–P coordination bond, leading to its capacity for the highly selective and effective accumulation of phosphate-contained biomolecules . On the basis of this feature, Mirkin et al fabricated the PO 4 3– -terminated DNA on the surface of UiO-66 nanoparticles, which was used to detect the cellular endotoxin.…”
mentioning
confidence: 99%
“…The results also showed that TMU‐5S preferentially binds to Ca 2+ over other metal cations at physiological concentrations, and exhibits a 5‐s response (the time required to obtain the 90% real value) and 40‐s recovery (the time for releasing up to 90% from a specific target). [ 125 ] The temporal responsiveness is sufficient for tracing slow Ca 2+ changes, but may be too protracted for fast‐tracking or instantaneous reading of [Ca 2+ ] changes.…”
Section: The State‐of‐the‐art Sensors For [Ca2+]exmentioning
confidence: 99%